On the Magnification of Small Biases in Hiring - DAVIES, SHAUN WILLIAM; WESEP, EDWARD D. VAN; WATERS, BRIAN (Journal of Finance, 2024)
ABSTRACT We analyze a setting in which a board must hire a chief executive officer (CEO) after exerting effort to learn about the quality of each candidate. Optimal effort is asymmetric, implying asymmetric likelihoods of each candidate being chosen. If the board has an infinitesimal bias in favor of one candidate, it allocates effort to maximize the likelihood of that candidate being chosen. Even when the board's prior is that its preferred candidate is inferior, she may still be chosen most often. A glass ceiling can also arise whereby the tendency to hire favored candidates increases as the importance of the position increases.